Peasant Economy in Transition: Capitalism, Neoliberalism, and Rural Livelihoods in Nepal - Deo, Sachindra Kumar (Research Nepal Journal of Development Studies, 2025)
This term paper explores the transformation of the peasant economy in Nepal in the context of capitalism and neoliberalism, and how these global forces have reshaped rural livelihoods. Historically rooted in subsistence agriculture, Nepal’s peasant economy is increasingly subjected to market-driven reforms, land commodification, and policy-driven commercialization. Drawing on theoretical frameworks such as Marxian political economy and post-structuralist agrarian studies, and supported by secondary case-based evidence, the study analyzes the socio-economic impacts of structural adjustment, migration, and the decline of traditional farming practices. The findings reveal a dual rural economy marked by growing inequality, where a small segment benefits from agribusiness while the majority face marginalization, landlessness, and food insecurity. Despite government efforts through policies like the Agriculture Development Strategy (ADS), implementation remains weak due to institutional, political, and structural challenges. The study concludes with a call for inclusive land reform, participatory governance, rural employment diversification, and policies that prioritize social justice, gender equity, and sustainability to secure the future of Nepal’s peasant communities.